Empowering Village Communities in Kampar Regency, Indonesia based on Creative Economy: Collaborative Governance Approach - Ranggi Ade Febrian; Ahmad Fitra Yuza; Rendi Tri Afrianda; Adam Pratama Azwari (Borong Newinera Publisher, 2023)
The aim of this research is to determine the social and economic impact of community empowerment carried out by local governments through a creative economic approach. The research method used in this research is exploratory qualitative with a case study approach that occurred at the regional level with a collaborative governance pattern in community empowerment. This research was analyzed using Nvivo 12 Plus software. The results of this research show that firstly community empowerment through the creative economy in villages is hampered by problems such as limited infrastructure, lack of skills and training, market limitations, limited access to capital, inconsistent government support, intense competition, lack of awareness about creative service products, and geographical conditions. Therefore, researchers suggest that it is necessary to increase access to basic infrastructure such as electricity and internet, provide training in the field of marketing design, help access financing, support local government policies, market products and services based on e-commerce, build networks and collaborate with other creative economy entrepreneurs , involving local communities, and continuing to monitor and evaluate the success of creative economy initiatives in villages. This research contributes as a knowledge reference for overcoming social and economic problems in villages in Riau Province, Indonesia.